A Study of the Quench Sensitivity of 6061-T6 and 6069-T6 Aluminum Alloys. (19th May 2011) - Kassner, M. E.; Geantil, P.; Li, X.
Abstract : The purpose of this study is to investigate the quench sensitivity of the mechanical properties of 6061 and 6069 aluminum alloys. The relationship between mechanical properties and quench delay time at various temperatures between 200–500°C was determined. It was concluded that the 6069-T6 was somewhat more quench sensitive than 6061, which may be consistent with the composition difference. This study also provides increased data on the quench sensitivity of the traditional alloy, 6061-T6.